Peran Kurikulum dalam Pembelajaran PKN di Sekolah Dasar - Nurul Hermawati (LPPM Politeknik Pratama, 2024)
Citizenship Education (PKN) is one of the important subjects in elementary school (SD) which aims to form citizens who are intelligent, think critically and care about the nation and state. The role of the curriculum in PKN learning is very important, because the curriculum determines what is taught, how it is taught, and how learning outcomes are evaluated. This article discusses the role of the curriculum in PKN learning in elementary schools, including curriculum development, teaching, and evaluation of learning outcomes. Apart from that, this article also reviews some of the recent changes in the PKN curriculum in elementary schools and their impact on learning.